Effect of the number of exhaust fans on a rotary dryer for turmeric drying - I.B. Alit; I.G.B Susana; I.G.A.K.C. Adhi; S. Hidayatullah; E. Gunawan (Universitas Mataram, 2026)
One type of dryer frequently used in agricultural drying is the rotary dryer. When solids are dried in a rotary dryer, a transport phenomenon occurs that includes the simultaneous transfer of mass, heat, and momentum. This study aims to determine the effect of the number of exhaust fans on the drying performance of turmeric using a rotary dryer. The number of exhaust fans used varied from 1, 2, and 3 units. The main parameters observed included the final moisture content, drying rate, and energy efficiency. The results showed that the use of one exhaust fan resulted in the lowest final moisture content compared to other configurations. During the 8-hour drying process, the rotary dryer with one exhaust fan was able to reduce the turmeric moisture content from 89% to 57.8%, with an average drying rate of 0.55 kg/hour. The use of one exhaust fan resulted in an optimal temperature range of 50–60°C. In addition, this configuration also showed relatively high energy efficiency, ranging from 10.8% to 25.5%. Therefore, the use of a single exhaust fan in a rotary dryer is considered the most optimal configuration in balancing the quality of drying results and energy efficiency.